Artist's Statement: Don't Lose Our Youth - Christopheraaron Deanes (Interdisciplinary Journal of Partnership Studies, 2022)
Artist’s Statement for the cover art of IJPS Volume 9, issue 1: Don’t Lose Our Youth, 2022. Oil, rice, gesso, and aerosol on wood.